REVITALISASI TRADISI MASSOLO PADA UPACARA KEMATIAN DI DESA BAEBUNTA (DALAM PERSPEKTIF DAKWAH) - Said, Muhazzab (Palita: Journal of Social Religion Research, 2017)
In the social sciences, tradition is defined as customs, religious rituals, and sacred ceremonies of a particular group of people. Massolo' in Baebunta is indeed a habit, customs, even can be said religious rituals performed on every death of a family member. Based on the purpose and usefulness, massolo tradition 'is a positive thing, because in it there are elements of help to help each other as long as the action is based on sincere intention and not forced. But whatever the motive, the massolo’ tradition needs to be revitalized, straightened and preserved.